C Source Code Auto Review Tool for Secure Programming of Indian Spacecraft Ground Software Elements, GEOSCHEMACS (International Journal of Engineering and Computer Science, 2015)
Secure software development involves practicing secure programming constructs and standards. To enable the software is developed with secure programming standards, secure static analysis play major role in finding out the hidden vulnerabilities in the source code. Secure static analysis tools yield significant reduction in runtime failures of the software. GEOSCHEMACS (Geostationary Earth Orbit SpaceCraft HEalth Monitoring, Analysis and Control Software) is Indian Spacecrafts primary ground software element and developed mostly based on C programming language. The aim of this paper was to discuss the development of software for auto reviewing of C source code. The paper highlights the necessity of a customized & proprietary tool in complying against CERT (Computer Emergency Response Team) C secure coding standard and enhancing the secure software development of GEOSCHEMACS. It brings out the design and test results of the tool.